2017
DOI: 10.1186/s40359-017-0184-1
|View full text |Cite
|
Sign up to set email alerts
|

A case matched study examining the reliability of using ImPACT to assess effects of multiple concussions

Abstract: BackgroundApproximately 3.8 million sport and recreational concussions occur per year, creating a need for accurate diagnosis and management of concussions. Researchers and clinicians are exploring the potential dose-response cumulative effects of concussive injuries using computerized neuropsychological exams, however, results have been mixed and/or contradictory. This study starts with a large adolescent population and applies strict inclusion criteria to examine how previous mild traumatic brain injuries af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Cerebral concussion caused by traumatic biological force can produce complex effects on the brain, causing a series of pathophysiological reactions and leading to rapid and transient neurological impairment. With the increasing number of trauma, it will further lead to severe damage to learning and memory abilities and balance motion behavior ( 9 , 10 ). Benson et al ( 11 ) studied and found that when cerebral concussion in patients has not restored, the stimulation of cerebral concussion once again can lead to learning and memory and neurological disorders in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral concussion caused by traumatic biological force can produce complex effects on the brain, causing a series of pathophysiological reactions and leading to rapid and transient neurological impairment. With the increasing number of trauma, it will further lead to severe damage to learning and memory abilities and balance motion behavior ( 9 , 10 ). Benson et al ( 11 ) studied and found that when cerebral concussion in patients has not restored, the stimulation of cerebral concussion once again can lead to learning and memory and neurological disorders in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In one validation of the ImPACT neurocognitive screen, the authors carefully selected a sample of 303 athletes from a pool of 26,240 athletes, ages 10 to 19 years. The authors identified baseline data and delineated patterns of postconcussion symptom expression (Barker et al, 2017). In a separate study, the sensitivity and specificity of the ImPACT screen had only minimally acceptable discriminant function analysis results.…”
Section: Category 1: Cognitive and Behavioralmentioning
confidence: 99%
“…10,11 Recent research has continued to emphasize that accounting for such concussion co-morbidities is critical to the proper interpretation of neuropsychological test results. 12 Nuwer et al explain that "Concussion symptoms can be difficult to separate from ADHD baseline symptoms… Many postconcussion symptoms present as a clinical picture similar to ADHD itself." 13 The Institute of Medicine and National Research Council of the National Academies ("IOM-NRC") report titled Sports-Related Concussion in Youth: Improving the Science, Changing the Culture, identifies ADHD and learning disabilities as co-morbid conditions in neuropsychological testing and recommends collection of such data in concussion evaluation, noting that the presence of these factors may affect test outcomes.…”
Section: Cognitive Disorders As Modifying Factors In Concussion Researchmentioning
confidence: 99%